Successful Treatment With Omalizumab in a Child With Asthma and Urticaria: A Clinical Case Report - Sirufo, Maria Maddalena; Ginaldi, Lia; De Martinis, Massimo (Frontiers in Pediatrics, 2019)
Urticaria of childood is rare and more uncommon is its persistence.Comorbidities are associated with CSU in children, among these asthma, allergic rhinitis or atopic dermatitis, while many children with CSU have a family history of atopy. Therapeutic approach to CSU in children is the same recommended in international guidelines for management of chronic urticaria in adults. In the European Union, according to European Medicine Agency, Omalizumab is indicated as add-on therapy for the treatment of chronic spontaneous urticaria in adult and adolescent (12 years and above) patients with inadequate response to H1 antihistamine treatment. Furthermore in children (6 to <12 years of age) is indicated as add-on therapy to improve asthma control.The treatment of children with urticaria under the age of 12 represents a therapeutic “limbo”, being possible to administer omalizumab only “off label”.